ChatGPT as an Interactive Dictionary for Mahārah Kitābah Learning: A Literature Review - Viqri Aditya; Zulhannan Zulhannan; Fachrul Ghazi; Koderi Koderi; Guntur Cahaya Kusuma (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study explores the role of ChatGPT as an interactive dictionary in enhancing mahārah kitābah (Arabic writing skills) learning. Arabic writing remains a challenging area due to learners’ limited vocabulary, complex grammatical structures, and insufficient feedback, which highlights the necessity of adopting technology-based pedagogical solutions. To address these challenges, a Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines to ensure methodological rigor and transparency. The review analyzed 15 peer-reviewed studies published between 2020 and 2025, systematically selected from Scopus, Google Scholar, and ResearchGate using predefined inclusion and exclusion criteria. The results demonstrate that ChatGPT substantially enhances vocabulary retention (reported in seven studies), improves grammatical accuracy (five studies), and promotes learner motivation and autonomy (four studies). Despite these advantages, the findings also reveal challenges, including the risk of overreliance on AI-generated input and the need for teacher scaffolding to sustain creativity and critical thinking. In conclusion, ChatGPT shows strong potential as an interactive dictionary for supporting mahārah kitābah within digital Arabic language education. The study contributes by synthesizing current empirical evidence and offering pedagogical insights for integrating artificial intelligence into Arabic language curricula in a balanced, ethical, and effective manner.